Determinants of customer satisfaction and loyalty Waroeng Steak Restaurant in DKI Jakarta - Endang Saefuddin Mubarok; Budi Subarjo; Raihan Raihan; Wiwin Wiwin; Euis Bandawaty (Cogent Business & Management, 2023)
This study aims to determine the effect of facilities, brand image, product quality, promotion, and service quality on customer satisfaction and loyalty at Waroeng Steak Restaurants in DKI Jakarta. This research design is descriptive and quantitative explanatory, with a multivariate analysis method. The research sample is 135 respondents. Data were collected with a questionnaire instrument and analyzed with a structural equation model. The results of this study concluded that; facilities have a significant effect on customer satisfaction but have no significant effect on customer loyalty, brand image has a significant effect on customer satisfaction but has no significant effect on customer loyalty; product quality has a significant effect on customer satisfaction, and customer loyalty; promotion has no significant effect on customer satisfaction and customer loyalty; service quality has a significant effect on customer satisfaction, but has no significant effect on customer loyalty and customer satisfaction has a significant effect on customer loyalty.
Keywords: 650; brand image; facilities; loyalty; product quality; promotion; satisfaction; service quality